Safety and Visual Outcome of Visian Toric ICL Implantation after Corneal Collagen Cross-Linking in Keratoconus: Up to 2 Years of Follow-Up - Rafic Antonios; Ali Dirani; Ali Fadlallah; Elias Chelala; Adib Hamade; Carole Cherfane; Elias Jarade (Journal of Ophthalmology)
Purpose. To evaluate the long-term safety and clinical outcome of phakic Visian toric implantable collamer lens (ICL) insertion after corneal collagen cross-linking (CXL) in progressive keratoconus. Methods. This was a retrospective study of 30 eyes (19 patients), with progressive keratoconus, who underwent sequential CXL followed by Visian toric ICL implantation after 6 months. Results. At baseline, 6 eyes had stage I, 14 eyes stage II, and 10 eyes stage III keratoconus graded by Amsler-Krumeich classification. At 6 months after CXL, only K (steep) and K (max) decreased significantly from baseline, with no change in visual acuity or refraction. Flattening in keratometric readings was stable thereafter. There was significant improvement in mean uncorrected distance visual acuity (1.57 ± 0.56 to 0.17 ± 0.06 logMAR, P<0.001) and mean corrected distance visual acuity (0.17 ± 0.08 to 0.11 ± 0.05 logMAR, P<0.001) at 12 months after ICL implantation that was maintained at the 2-year follow-up. Mean cylinder power and mean spherical equivalent (SE) also decreased significantly after ICL implantation. A small hyperopic shift in SE (+0.25 D) was observed at 2 years that did not alter visual outcomes. Conclusions. Visian toric ICL implantation following CXL is an effective option for improving visual acuity in patients with keratoconus up to 2 years.